A note on the application of post-randomization adjustment - Chen, Xun (Henry Stewart Talks, 2007)
Adjustment for post-randomization variables: uses in practice to obtain additional information in randomized experiments, Potential problems of the conventional regression based post-randomization adjustment method: reliability, precision and causality, Available alternative methods that could provide either more powerful, less biased evaluation or more appropriate assessment for causality, Examples of the application of the different post-randomization adjustment methods
Archived at 2018/05/31